Dakwah Pesantren Menangkal Paham Radikalisme dengan Wawasan Al-Qur`An dalam Khutbah Jum’at (Studi Analisis Fungsi Utama Khutbah Jum’at) - Imam Syafi’i; Abdul Aziz (Islam Universalia: International Journal of Islamic Studies and Social Sciences, 2022)
This study is to examine the main function of Friday sermons and Islamic boarding schools in countering radicalism. The main reason for the existence of radicalism is the lack of religious understanding, especially regarding the verses of the Qur'an and Hadith which are only understood textually and are truncated. This happens because of the lack of exploring and comprehensively reviewing the contents of the Qur'an. One of the important moments to convey religious knowledge in the midst of society is the Friday sermon which has become a routine for every Friday prayer. Where maybe only this weekly opportunity they can gather and attend the majlis in the midst of their busy lives. Here, Islamic boarding schools as educational institutions in transforming scientific values and exemplary, are urgently needed to provide role models and become examples of how the Friday sermon theme delivered relates to explanations related to religious texts (al-Qur'an and Hadith), namely explaining the content of the Qur'an, especially those related to radicalism, which is widely misunderstood. In addition, pesantren can unite Muslims in following the correct rules of understanding the Qur'an and Hadith.